2018
DOI: 10.1177/1524838018813204
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Needs and Lived Experiences of Racial and Ethnic Minority Domestic Violence Survivors Through Community-Based Participatory Research: A Systematic Review

Abstract: Community-based participatory research (CBPR) is a methodological approach where community–academic teams build equitable relationships throughout the research process. In the domestic violence (DV) field, CBPR may be particularly important when conducting research with racial and ethnic minority DV survivors, as this group faces concurrent oppressions that inform their lived experiences. To our knowledge, no systematic review has synthesized articles using a CBPR approach to explore the needs and lived experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 42 publications
(185 reference statements)
1
33
0
Order By: Relevance
“…One such time of increased stress has been the coronavirus 2019 (COVID-19) pandemic, which has created devastating health and economic impacts globally (Bauer et al, 2021 ). In the early stages of the pandemic, a flurry of commentaries and lay press articles expressed concern about increased IPV frequency and severity due to the multiple interweaving impacts of the pandemic, compounded with widespread physical distancing measures (Campbell, 2020 ; Evans et al, 2020 ; Ragavan et al, 2020a ; Ragavan et al, 2020b ; United Nations, 2021 ). A recent meta-analysis of studies examining IPV during the COVID-19 pandemic reported that most study estimates were indicative of an increase in IPV during the pandemic (Piquero et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…One such time of increased stress has been the coronavirus 2019 (COVID-19) pandemic, which has created devastating health and economic impacts globally (Bauer et al, 2021 ). In the early stages of the pandemic, a flurry of commentaries and lay press articles expressed concern about increased IPV frequency and severity due to the multiple interweaving impacts of the pandemic, compounded with widespread physical distancing measures (Campbell, 2020 ; Evans et al, 2020 ; Ragavan et al, 2020a ; Ragavan et al, 2020b ; United Nations, 2021 ). A recent meta-analysis of studies examining IPV during the COVID-19 pandemic reported that most study estimates were indicative of an increase in IPV during the pandemic (Piquero et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…We frame these needs within the intersectionality framework, recognizing that forms of structural oppression such as sexism, racism, classism, and xenophobia profoundly influence people's identities and intersect to create varying degrees of privilege. [30][31][32] We by no means discuss every group of marginalized survivors but hope to provide a brief overview.…”
Section: Addressing Ipv Among Marginalized Populationsmentioning
confidence: 99%
“…35 Immigrant survivors may also face discrimination and stigma both within and outside of their communities. 30,36 Clinicians should ask survivors about their individual preferences for culturally specific IPV agencies, where available. Supporting the unique needs of immigrant children and adolescents (who comprise 25% of the US child population) exposed to IPV may require special consideration.…”
Section: Ipv In Immigrant Communitiesmentioning
confidence: 99%
“…Researchers must determine what methods to employ to arrive at the intended level of participation from community stakeholders (Chung & Lounsbury, 2006;Vaughn & Jacquez, 2020). Participatory approaches centralize sharing power and collaborative decision-making between community partners and academic partners throughout the research process, from conceptualization to analysis to dissemination of study findings (Israel et al, 2008;Ragavan et al, 2020). In traditional community-based participatory research (CBPR), academic partners approach community partners -and sometimes, but less often, vice versa -to establish a connection around conducting research on a topic of shared interest (Duran et al, 2012).…”
mentioning
confidence: 99%